High-sensitivity c-reactive protein and cardiovascular disease risk assessment in a population of type 2 diabetes mellitus patients - Bruno Basil; Jamila Aminu Mohammed; Izuchukwu Nnachi Mba; Blessing Kenechi Myke-Mbata; Joseph Chizoba Akujieze (BMC Cardiovascular Disorders)
Abstract Background Cardiovascular disease (CVD) remains the leading cause of mortality in individuals with type 2 diabetes mellitus (T2DM), driven by chronic hyperglycaemia, dyslipidaemia, and systemic inflammation. In Nigeria, genetic predispositions, ethnic and environmental factors may further modulate CVD risk. This study aimed to evaluate the association between high-sensitivity C-reactive protein (hsCRP) and CVD risk in Nigerian T2DM patients receiving standard care. Methods This cross-sectional hospital-based study was conducted over 13 months. Data on socio-demographic characteristics, medical history, clinical findings, and laboratory parameters were collected using a structured proforma. Serum hsCRP was measured by homogenous immunoassay, while 10-year CVD risk was estimated with the WHO CVD risk assessment chart validated for Western sub-Saharan Africa. Statistical analyses, including binary logistic regression to assess the association between hsCRP and CVD risk, were conducted using SPSS version 25, with significance set at p < 0.05. Results Moderate-to-high CVD risk was prevalent in 51.5% of the study population. Longer diabetes duration (AOR = 1.345, 95% CI: 1.222–1.480, p < 0.001), elevated HbA1c (OR = 1.438, 95% CI: 1.061–1.949, p = 0.019), and co-morbid hypertension (OR = 14.498, 95% CI: 2.611–80.515, p = 0.002) were significantly associated with higher CVD risk. Serum hsCRP levels were higher in moderate-to-high-risk individuals (median: 2.42 mg/L, IQR: 2.8; 2.71 mg/L, IQR: 1.8) compared to lower-risk individuals (median: 1.22 mg/L, IQR: 2.5; 1.48 mg/L, IQR: 2.6), p = 0.012. However, it was not an independent predictor of CVD risk after adjusting for confounders (p = 0.369). Conclusion There is a high burden of increased CVD risk in this population despite ongoing management, with prolonged diabetes duration, poor glycaemic control and co-morbid hypertension as key predictors. Although hsCRP levels were elevated in higher-risk individuals, its clinical utility as an independent predictor of CVD risk may be limited. These findings emphasize the need to strengthen routine CVD risk assessment, prioritize modifiable risk factors, and optimize glycaemic control to reduce CVD burden in Nigerian T2DM patients.